AN EXPERIMENTAL AND NUMERICAL STUDY OF LAMINAR NATURAL CONVECTION IN A DIFFERENTIALLY-HEATED CUBICAL ENCLOSURE - Kurekci, N. Alpay; Ozcan, Oktay (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2012)
Natural convection of air in a cubical cavity was investigated experimentally and numerically. A cubical enclosure of 200x200x200 mm(3) dimensions was considered. One vertical wall of the cavity was hot, the opposite one was cold and the rest of the walls were adiabatic. Three walls were made of aluminum, whereas the remaining three walls were made of heat-resistant glass. Temperature of the hot wall was kept constant by means of an electrical heater and the cold wall was cooled by ambient air in the experiments. Particle Image Velocimetry (PIV) was used for velocity measurements and Fluent CFD software package was employed for the numerical solution of three-dimensional laminar flow equations at a Rayleigh number of 1.3x10(7). The numerical and experimental results were compared and found to be in general agreement with each other. Suitability of a characteristic velocity for normalizing velocity data obtained was demonstrated.
Keywords: Natural convection; Enclosure; Ply; CFD; Laminar flow; AIR-FLOW; SIMULATION; CAVITY; Thermodynamics; Engineering